No coupling, no decoupling, only mutual inter-dependence: Business cycles in emerging vs. mature economies - Pierre L. Siklos (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
Even before the events of the past few years, economists and policy makers were musing about the apparent contradiction between globalization, as it is generally understood, and the seemingly different paths in overall economic activity taken by the emerging and more mature economies of the world. The present paper reconsiders whether it is, in fact, useful to think of correlations in business cycle movements as reflecting some form of coupling or decoupling and, instead, suggests that, even if business cycles may well have become more synchronous for a time, it is more useful to think of international business cycle co-movements as reflecting their mutual dependence that can be subjected to short-run interruptions or affected by a variety of other economic factors. I report evidence based on factor-augmented quantile regressions for a panel of annual data since 1980 from 9 regions of the world. A panel is used to estimate the common factors which are then applied to the quantile regression model to determine the sources of business cycle co-movements across countries and regions of the world.
URN:NBN:fi:bof-201408072133
Keywords: E32; C21; C22; C23; 330; business cycles; quantile regression; panel estimation; factor model; coupling; decoupling